Karakteristik Perusahaan dan Pengungkapan Corporate Social Responsibility Dimoderasi Good Corporate Governance terhadap Nilai Perusahaan - Novi Yanti; Sarwani Sarwani; Novika Rosari (Universitas Winaya Mukti, 2021)
Company value is considered necessary for interested parties both internally and externally when making investments. This study examines and analyzes the influence of Company Characteristics (Firm Size, Capital Structure, and Profitability) and Corporate Social Responsibility (CSR) Disclosure moderated by Good Corporate Governance on Firm Value. There are 188 manufacturing companies on the Indonesia Stock Exchange (IDX), the population with 22 sample companies in the 2016-2018 period. The sampling technique was the purposive sampling method. Data were analyzed using multiple linear regression and moderated regression analysis on SPSS. This study indicates that the capital structure and good governance affect firm value, and the firm size variable shows a negative effect. Good Corporate Governance can strengthen the influence of firm size, capital structure, and CSR disclosure on firm value, while good governance weakens the effect of profitability on firm value, which is of interest.